2009
DOI: 10.1038/jhh.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene and retinal arteriolar narrowing: The Funagata Study

Abstract: The purpose of this study is to determine whether the angiotensin-converting enzyme (ACE) gene polymorphism is associated with retinal arteriolar narrowing, a subclinical marker of chronic hypertension. The Funagata Study examined a population-based sample of Japanese aged 35+ years; 368 participants had both retinal vessel diameter measurements and ACE insertion/deletion (ACE I/D) polymorphism analyses performed. Assessment of retinal vessel diameter and retinal vessel wall signs followed the protocols used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…31 Newer data also suggest that angiotensin-converting enzyme I/D gene polymorphism may be associated with subclinical structural arteriolar changes related to chronic hypertension among the Japanese. 32 Retinal vascular imaging Novel computer-based imaging analysis allows quantification of subtle hypertensive retinopathy changes. 33 Previous studies have already shown retinal arteriolar diameter is strongly and inversely associated with elevation of blood pressure, reflecting systemic peripheral vasoconstriction.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…31 Newer data also suggest that angiotensin-converting enzyme I/D gene polymorphism may be associated with subclinical structural arteriolar changes related to chronic hypertension among the Japanese. 32 Retinal vascular imaging Novel computer-based imaging analysis allows quantification of subtle hypertensive retinopathy changes. 33 Previous studies have already shown retinal arteriolar diameter is strongly and inversely associated with elevation of blood pressure, reflecting systemic peripheral vasoconstriction.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…167 The angiotensin-converting enzyme gene polymorphism has also been linked with retinal arteriolar narrowing. 168 Others studies have reported isolated genetic loci associated with retinal arteriolar calibre and hypertensive retinopathy signs. 169,170 Future genetic studies on hypertensive eye disease, including whole exome or genome studies and mendelian randomisation, may provide novel insights into the contribution of genetic mechanisms on the microcirculatory changes of hypertension and CVD.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…In a relatively small study of 368 participants of the Funagata study, Tanabe et al . [60]. reported that retinal arteriolar diameter was significantly narrower in individuals with the deletion (D/D) genotype of the angiotensin‐converting enzyme (ACE) gene compared to individuals with insertion/deletion (I/D) or insertion (I/I) genotypes after multivariable adjustment.…”
Section: Genetic Influences On the Retinal Microcirculationmentioning
confidence: 99%